2021
DOI: 10.5114/bta.2021.106525
|View full text |Cite
|
Sign up to set email alerts
|

Identification of putative miRNAs from Expressed Sequence Tags of Gnetum gnemon L. and their cross-kingdom targets in human

Abstract: Wild edible plants are often found to be rich sources of nutrients and medicinally beneficial compounds with pharmacological activities. Gnetum gnemon is a nutritionally important plant and a popular food source in parts of Assam and North-East India. Various microRNAs (miRNAs) have been recently identified in many plants; however, there are no records of identification of miRNAs in any species of Gnetum . The prediction of miRNA-target associations in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 58 publications
0
1
0
Order By: Relevance
“…The compound was shown to have tyrosinase inhibitory activity 16 . MicroRNA analysis of G. gnemon indicated that this plant has the potential to be used as a small-RNA based treatment for particular human diseases 17 .…”
Section: Introductionmentioning
confidence: 99%
“…The compound was shown to have tyrosinase inhibitory activity 16 . MicroRNA analysis of G. gnemon indicated that this plant has the potential to be used as a small-RNA based treatment for particular human diseases 17 .…”
Section: Introductionmentioning
confidence: 99%